Implementation Of Corporate Social Responsibility (CSR) In Improving The Community's Economy In The Concept Of Falah - Ariyadi Ariyadi; Nurlaila Nurlaila; Aqwa Naser Daulay (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research was conducted to find out how the implementation of the Corporate Social Responsibility (CSR) program of PT Buana Wiralestari Mas in increasing the economic income of the community in Kampar Regency, Riau and how the implementation of the Corporate Social Responsibility (CSR) program of PT Buana Wiralestari Mas in the concept of Falah. The research method used in this research is quantitative descriptive method. The method used in descriptive research is the survey method and uses online questionnaires as the main media for data collection. Respondent characteristics include gender, age, and education level. The census technique was used to sample the entire population of the community who received the CSR program, which amounted to 30 individuals. The results of this study indicate that the Corporate Social Responsibility (CSR) program implemented by PT Buana Wiralestari Mas has a significant impact in improving the community's economy. Based on the concept of Falah (Welfare), the CSR program of PT Buana Wiralestari Mas succeeded in improving the welfare of the community by fulfilling the four main elements in Falah, namely the spiritual aspect (Tawhid), survival, freedom of will, strength and self-esteem.